Creation of an Artificial Layer for Boosting Zn2+ Mass Transfer and Anode Stability in Aqueous Zinc Metal Batteries - Tang, Mingcong; Liu, Qun; Liu, Gang; Zou, Xiaohong; Zhang, Kouer; Yu, Zhenlu; Zhang, Biao; An, Liang (Nano-Micro Letters, 2026)
Aqueous zinc metal batteries (AZMBs) are promising candidates for next-generation energy storage, but their commercialization is hindered by zinc anode challenges, notably parasitic reactions and dendrite growth. Herein, we present a biodegradable biomass-derived protective layer, primarily composed of curcumin, as a zincophilic interface for AZMBs. The curcumin-based layer, fabricated via a homogeneous solution process, exhibits strong adhesion, uniform coverage, and robust mechanical integrity. Rich polar functional groups in curcumin facilitate homogeneous Zn2+ flux and suppress side reactions. The curcumin-based layer shows a favorable affinity for zinc trifluoromethanesulfonate (Zn(OTf)2) electrolyte, which is the representative of organic zinc salts, enabling optimal thickness for both protection and ion transport. The protected Zn anodes demonstrate an extended lifespan of 2500 h in symmetrical cells and a high Coulombic efficiency of 99.15%. Furthermore, Zn(OTf)2-based system typically exhibits poor stability at high current densities. Fortunately, the lifespan of symmetrical cells was extended by 40-fold at the high current density. When paired with an NaV3O8·1.5H2O (NVO) cathode, the system achieves 86.5% capacity retention after 3000 cycles at a large specific current density of 10 A g−1. These results underscore the efficacy of the curcumin-based protective layer in enhancing the reversibility and stability of metal electrodes, specifically relieving the instability of Zn(OTf)2-based systems at high current densities, advancing its commercial viability. Highlights: 1 Natural extract, curcumin, was employed as the protective layer to improve the zinc anode stability. 2 The curcumin-based layer balanced the efficient thickness, robust adhesion, and facilitated Zn2+ transportation. 3 The desolvation mechanism with a metal ion chelating agent aside was clearly elucidated.